Answer:
x = -11
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
3 + 3(x + 2) = -24
Step 2: Solve for x
- Distribute 3: 3 + 3x + 6 = -24
- Combine like terms: 3x + 9 = -24
- Isolate x term: 3x = -33
- Isolate x: x = -11
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 3 + 3(-11 + 2) = -24
- Add: 3 + 3(-9) = -24
- Multiply: 3 - 27 = -24
- Subtract: -24 = -24
Here we see that -24 does indeed equal -24.
∴ x = -11 is the solution to the equation.